2020
DOI: 10.1016/j.culher.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach for assessing the vulnerability of World Heritage Sites to climate change impacts

Abstract: One of the most difficult problem facing those responsible for managing World Heritage Sites (WHS) is climate change, as it poses continuous new challenges to the conservation of cultural heritage. Moreover, as our climate continues to change our cultural heritage will potentially be exposed to diverse pressures and potentially to risks not previously experienced. Thus, management practices will need to be tailored in order to include climate change impacts. For climate change impacts to be incorporated into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 37 publications
0
47
0
2
Order By: Relevance
“…Its natural exposure to increased environmental pressures and historical protection requirements often limit the enhancement of its material performance [28]. Thus, many scholars have begun fragility research of the historic environment, investigating various disasters including climate disasters [29], geological disasters [30], fires [31], earthquakes [32,33], floods [34] as well as marine and aeolian processes [35].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Its natural exposure to increased environmental pressures and historical protection requirements often limit the enhancement of its material performance [28]. Thus, many scholars have begun fragility research of the historic environment, investigating various disasters including climate disasters [29], geological disasters [30], fires [31], earthquakes [32,33], floods [34] as well as marine and aeolian processes [35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, these studies mainly focused on subjects with a high level of historic environmental protection such as world heritage sites [29,30] and famous historical and cultural cities [33]. Relatively little concern has been expressed for the historic environmental vulnerability of villages, especially traditional villages.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it follows recognising that in addition to 'the overarching objective of safeguarding the outstanding universal values of WH properties', these properties must 'serve as laboratories where monitoring, mitigation and adaptation processes can be applied, tested and improved' [5]. However, recent studies [3,6,7] found that heritage conservation practice has primarily focused on reactive measures that are taken after climate change impacts occur; these impacts include damage or loss to heritage properties [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to changes in climatic conditions demonstrated in recent years, with a consequent increase in the frequency and intensity of extreme weather phenomena, hydrogeological instability is causing increasing damages to cultural heritage [4] [5] [10]. This has a potential impact on the built and landscape heritage, which frequently fails to have appropriate protection systems [14] [18] [19] [20].…”
Section: Introductionmentioning
confidence: 99%